Penerapan Strategi Promotion Mix Pada Warung Makan Mie Residivis Untuk Meningkatkan Daya Saing - Listia Nurjanah; Yosep Dwi Rian (ConCEPt - Conference on Community Engagement Project, 2021)
Promotion can be done in various ways, one of which is using digital or non-digital media, every UMKM competes to find consumers by doing the right promotion. Mie Residivis have food products with spicy flavors that are already doing quite a promotion, but the promotion itself has not been able to make the products dominate the market. The purpose of the study was to measure the extent of influence in terms of reach, engagement, reaction, analyzing the effectiveness of ads on Instagram Stories, Facebook posts, brochures, and banners. The implementation of the promotion mix strategy can provide an overview of the Mie Residivis on how to promote effectively in marketing. The results of implementing this new strategy indicate that there is a significant increase in the number of visitors/buyers.